Starvation percentages in field caught Sardina pilchardus larvae off southern Portugal - Teodosio, Maria (1997)
Starvation has been proposed as a major event only in small larvae that are learning to feed on planktonic prey. However, there are few comparisons of percentages of starving larvae either among locations, times or phases of larval development. The percentage of starvation of Sardina pilchardus larvae of different lengths was analysed in four distinct areas off southern Portugal. A highly sensitive fluorometric method for RNA/DNA quantification was applied to field caught S. pilchardus larvae during April and May 1992. Using in situ determination of critical RNA/DNA ratio (1.3), we classified as starving only a small percentage (2.22%) of first-feeding (<8 mm) sardine larvae, but bigger larvae appeared to be more vulnerable to starvation. We concluded that sardine larvae analysed were generally in good condition (total percentage of starving larvae - 4.64%), but with some variation within each region.